2013
DOI: 10.3892/ol.2013.1751
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Notch1 intracellular domain and p21 proteins, and their clinical significance in gastric cancer

Abstract: Changes in the expression of the Notch1 intracellular domain (NICD) and p21 proteins have been shown to be closely associated with the development and progression of a number of cancers. The present study aimed to investigate the expression levels of the two proteins in gastric carcinoma and precancerous lesions, and to determine the clinical significance of this. A total of 109 gastric cancer, 57 precancerous gastric lesion, 50 chronic superficial gastritis and 17 normal gastric mucosa patients were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
2
17
2
1
Order By: Relevance
“…We found that Notch1 controls HEp-2 cell migration and invasion, although the underlying molecular mechanism remains unclear. Luo et al found that inhibition of NICD decreased tumor invasion in gastric cancer (30). Zhou et al reported that downregulation of Notch1 decreased HCC cell migration and invasion by regulating E-cadherin and CD44v6 (31).…”
Section: Discussionmentioning
confidence: 99%
“…We found that Notch1 controls HEp-2 cell migration and invasion, although the underlying molecular mechanism remains unclear. Luo et al found that inhibition of NICD decreased tumor invasion in gastric cancer (30). Zhou et al reported that downregulation of Notch1 decreased HCC cell migration and invasion by regulating E-cadherin and CD44v6 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies implicate Notch signalling in essentially all of the hallmarks of cancer, being associated with abnormal expression, high mutation rate and poor survival in several cancers such as lung, breast, gastric or lymphoid cancer [7][8][9][10][11]. This oncogenic function of NOTCH in human cancers is related with its capacity to increase cell growth, centered on the ability to induce the expression of Myc [12,13] and to enhance PI3K-Akt signalling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant Notch signalling can often lead to the development of cancer. Our previous work showed that Notch1 intracellular domain (NICD) protein is overexpressed in GC tissues and is associated with overall patient survival, tumour metastasis and an advanced tumour stage [17]. In fact, expression of Notch1 and Hes1 was significantly higher in GC tissues than in normal tissues [18].…”
Section: Introductionmentioning
confidence: 99%